Dogs Naturally Infected with Hepatozoon spp. in the Sertão Paraibano Mesoregion, Brazilian Semiarid - Bernardino, Maria; Ângelo, Débora; Silva, Edijanio; Oliveira, Laura; Vaz, Antônio; Santos, Carolina; de Azevedo, Sérgio Santos (Acta Scientiae Veterinariae, 2024)
Background: Canine hepatozoonosis is a disease caused by protozoa of the genus Hepatozoon. It is transmitted when dogs ingest infected ticks and via the vertical route. In Brazil, it is often considered to be a subclinical disease, but it is still unclear whether more severe clinical signs develop in young, elderly or debilitating animals. The aim of this study was to report 82 cases of dogs naturally infected with Hepatozoon spp. in the Sertão mesoregion of Paraíba, in order to characterize the clinical signs, haematological findings, presence of concomitant diseases and epidemiological aspects. Cases: Records of 82 dogs that tested positive for Hepatozoon spp. in direct blood smears were studied. These animals were treated at the Veterinary Hospital of the Federal University of Campina Grande, located in the municipality of Patos, Paraíba, Brazil. The following data were obtained from each animal’s clinical record: age, sex, breed, presence of tick infestation, clinical signs and blood count data. According to the clinical findings, the animals were divided into 4 groups: 1- animals with co-infections; 2- with severe or debilitating conditions; 3- with non-specific clinical signs, and 4- asymptomatic. The most affected dogs were puppies up to 6 months old (P = 0.0002) and mixed breed (P = 0.0014). Infection was found in three puppies up to 30 days old. There was a high frequency of animals that presented ticks at the time of the clinical examination (P = 0.0006). Of the 82 positive dogs, 49 had severe or debilitating illnesses and were the most affected group (P < 0.001), 20 had non-specific clinical signs, 10 had co-infections with other agents and 3 were asymptomatic. The main conditions observed were trauma, neoplasms, co-infections with other haemoparasites and gastroenteritis. Anaemia and thrombocytopenia were the main haematological alterations, which were observed even in asymptomatic animals. Discussion: This is the 1st study to show that canine hepatozoonosis is present in the Sertão mesoregion of Paraíba, Northeast region of Brazil and to evaluate epidemiological aspects associated with the infection. The infection found in puppies suggests vertical infection. Diagnosis in this age group is extremely important, because in puppies the disease may present in an acute form, producing more severe clinical signs, due to the fact that immunity is not fully developed in these animals. Mixed breed dogs were more affected, which may be related to the fact that these animals belong to families with fewer socio-economic resources when compared to the owners of pedigree dogs, directly influencing basic care for the animal. Tick infestation was the main predisposing factor and highlights the need for owners to control ectoparasites. In most of the dogs the Hepatozoon spp. infection was not the main cause, presenting itself as a secondary laboratory finding. It is therefore possible that these associated diseases have reduced the resistance of the host’s immune system to Hepatozoon spp. There were also animals that presented only non-specific clinical signs that correlate with the pathogenesis of the parasite. Anaemia and thrombocytopenia were the main haematological alterations observed and proved to be indicative of Hepatozoon spp. infection, especially in subclinical cases. It is suggested that veterinary clinicians should request that blood smears be tested for Hepatozoon spp. in dogs with debilitating diseases, non-specific clinical signs or haematological disorders. Keywords: Canine hepatozoonosis, haemoparasites, anaemia, thrombocytopenia, vertical infection.